Mediastinal teratoma presenting with respiratory distress and cardiogenic shock in a neonate. (27th January 2020) - Stajevic, Mila; Dizdarevic, Ivan; Krunic, Igor; Topic, Vesna
Abstract: Mediastinal teratomas are uncommon, fast-growing thoracic tumours, which are usually diagnosed in childhood or adolescence. Neonatal forms are the rarest and often present with life-threatening respiratory distress syndrome. In our case, respiratory failure in a neonate was aggravated by severe cardiogenic shock due to aortic and systemic venous compression, extreme heart displacement and rotation, necessitating an emergency operation on the first day of life.